2019
DOI: 10.3389/fmars.2019.00163
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Deep-Sea Sponge Aggregations in an Area of Multisectoral Activities and Changing Oceanic Conditions

Abstract: Discovery and understanding of fragile deep-sea habitats like sponge aggregations, are being outpaced by anthropogenic resource exploitation. Sustainable ocean development in the Faroe-Shetland Channel Nature Conservation Marine Protected Area (FSC NCMPA; northeast Atlantic), which harbors sponge aggregations, now requires adaptive management in the face of encroachment of multisectorial activities in this area (e.g., fishing, oil and gas, shipping) and climate change. We examined sponge morphotype composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 65 publications
0
20
2
Order By: Relevance
“…Murillo et al, 2018 further noted that the structureforming Geodia species were found in areas with high primary production and fast currents that would provide the high food supply needed to reach their large biomasses. The importance of current regime and interactions between water masses has also been shown for the Faroe-Shetland Channel deep-sea sponge aggregations (Kazanidis et al, 2019), the Arctic sponge ground on the Schultz Seamount (Arctic Mid-Ocean Ridge; Roberts et al, 2018) and deep-sea aggregations of hexactinellids in the NE Atlantic (Rice et al, 1990;Barthel et al, 1996).…”
Section: Deep-sea Sponge Groundsmentioning
confidence: 81%
See 2 more Smart Citations
“…Murillo et al, 2018 further noted that the structureforming Geodia species were found in areas with high primary production and fast currents that would provide the high food supply needed to reach their large biomasses. The importance of current regime and interactions between water masses has also been shown for the Faroe-Shetland Channel deep-sea sponge aggregations (Kazanidis et al, 2019), the Arctic sponge ground on the Schultz Seamount (Arctic Mid-Ocean Ridge; Roberts et al, 2018) and deep-sea aggregations of hexactinellids in the NE Atlantic (Rice et al, 1990;Barthel et al, 1996).…”
Section: Deep-sea Sponge Groundsmentioning
confidence: 81%
“…One of the first reports of these habitats was by Rice et al (1990), who observed dense aggregations (density values ∼1.5 ind•m −2 ) of the hexactinellid Pheronema carpenteri (Figure 2) in the Porcupine Seabight (NE Atlantic). Subsequently, records of sponge grounds came both from the eastern (e.g., Klitgaard and Tendal, 2004;Howell et al, 2016;Roberts et al, 2018;Kazanidis et al, 2019) and western deep North Atlantic (e.g., Murillo et al, 2012Murillo et al, , 2016aMurillo et al, , 2018Knudby et al, 2013;Kenchington et al, 2014;Beazley et al, 2018). These included records not only of hexactinellids, but also of demosponges and especially those from the family Geodidae (Order Astrophorida, commonly known as ostur; Figure 2).…”
Section: Deep-sea Sponge Groundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying substratum and habitat-forming organisms provide a significant proportion of three-dimensional habitat in marine communities (Ferrari et al, 2016). Numerous studies have documented that structure-forming organisms such as sponges and CWC s play a key structural and functional role in the marine benthos, because they can modified physical properties of the sea floor and influence composition, abundance and distribution of epibenthic megafauna (Schlacher et al, 2007;Beazley et al, 2013;Howell et al, 2016;Huvenne et al, 2016;van den Beld et al, 2017;Kazanidis et al, 2019). Taxa identified in the NW limit of Guaymas basin and Sonoran Margin span several trophic levels including filter and suspension feeders, deposit feeders and carnivorous benthophages (Sokolova, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To aid the identification we supplemented these sources with a previous study that identified specimens of taxa collected during dive D347 (Villalobos Vazquez de la Parra, 2014). Additionally, to maximizes the comparability of our results with other studies, we grouped specimens and coverage data of sponges recorded in each benthic images into one of the following morphotypes categories based on the criteria proposed by Boury-Esnault and Rützler (1997) and Kazanidis et al (2019): amorphous, tubular and clavate ("club-shaped") (see the sponge morphotype examples provide as Supplementary Material). Taxonomic richness described the total number of morphospecies per image.…”
Section: Video and Image Analysismentioning
confidence: 99%